A Lemierre syndrome variant caused by Klebsiella pneumoniae - Yih-Jeng Tsai; Yu-Chi Lin; Dor-Ji Harnnd; Rayleigh Ping-Ying Chiang; Hsing-Mei Wu (Journal of the Formosan Medical Association, 2012)
Lemierre syndrome is an extremely rare disease characterized by oropharyngeal infection, septicemia, internal jugular vein thrombosis, and skip lesions. The most common causative pathogen is Fusobacterium necrophorum. We reported a 45-year-old woman who presented with left neck painful swelling and septicemia. Magnetic resonance imaging of the head and neck demonstrated venous thrombosis extending from the left internal jugular vein to the sigmoid sinus. During admission we discovered that the patient had uncontrolled diabetes mellitus. We also found a metastatic lesion through chest radiography. Klebsiella pneumoniae was cultivated from both blood samples and pus from deep neck spaces. Surgical drainage, early and adequate antibiotic treatment, anticoagulation, and strict control of blood glucose led to the patient's complete recovery. Because Lemierre syndrome is a forgotten disease in the era of antibiotics, awareness of the signs and symptoms of this disease is important because of its associated high mortality rate. This case illustrated that the presence of K pneumoniae can lead to Lemierre syndrome.